Economic Analysis of Front Line Demonstrations on Cumin: A Case in Arid Zone of Rajasthan - Choudhary, M K; Singh, Dheeraj; Meena, M L; Tomar, P K (Annals of Arid Zone, 2016)
Cumin is a predominantly rabi crop in arid zones of Rajasthan. The crop accounts for 32.21 and 18.09% of area and production, respectively, in Rajasthan. The average yield of the crop is 776 kg ha-1 in Pali district, which is substantially lower than the national average (1245 kg ha-1). Considerable scope for enhancement in productivity exists, especially in Pali district, which is an important agro export zone for cumin in the country. The paper draws upon the data from 65 Front Line Demonstrations (FLDs) organized by KVK, CAZRI, Pali, between 2005-06 and 2009-10 at five locations under actual farm situations. The economics and cost benefit ratio of both control and demonstration plot was worked out. An average net profit of Rs. 92,700 ha-1 was recorded under recommended practices whereas the net profit was Rs. 61,606 ha-1 under farmer’s practice. The range of cost benefit ratio was 2.02-3.94 under demonstration, while it was 1.49-2.86 under control plots. The results showed that adoption of improved technology can enhance productivity of cumin in arid region while increasing the profitability of cultivation for the farmers. Key words: Technology, impact, FLD, cost benefit ratio, cumin.